IMPLEMENTASI BIOSEKURITI PADA USAHA BUDIDAYA AYAM KUB: UPAYA PENCEGAHAN PENYAKIT DAN PENINGKATAN KUALITAS HASIL TERNAK - Detha, Annytha Ina Rohi; Foeh, Nancy Diana Frederika Katerina; Ndaong, Nemay Anggadewi (Universitas Nusa Cendana, 2025)
The cultivation of Kampung Unggul Balitbangtan (KUB) chickens presents significant potential for enhancing community economic welfare, particularly in improving family nutrition in rural areas. Nevertheless, a major challenge faced by partner farmers is the limited knowledge of proper KUB chicken farming techniques, including maintenance practices and the implementation of biosecurity measures. This community service initiative aimed to improve farmers' understanding and skills in applying biosecurity principles to prevent disease outbreaks and enhance livestock production quality. The program employed a combination of educational seminars, hands-on training sessions, and intensive group mentoring. The outcomes demonstrated a notable improvement in farmers' awareness of the importance of biosecurity, positive shifts in the application of best practices for KUB chicken management, and a reduction in livestock disease incidence. This initiative is expected to contribute to the development of sustainable, healthy, productive, and competitive KUB chicken farming enterprises.